2020
DOI: 10.1002/ese3.619
|View full text |Cite
|
Sign up to set email alerts
|

Using seasonal temperature difference in underground surrounding rocks to cooling ventilation airflow: A conceptual model and simulation study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The differences mentioned above cause changes in the heat balance by comparison with the areas surrounding the city. The city heats itself slowly, stores more heat overall, and passes it on again slowly to the surrounding areas, i.e., it can generally be considered an enormous heat storage unit [90,91]. Over the long term, this process increases the annual mean air and soil temperatures.…”
Section: Physical Chemistrymentioning
confidence: 99%
“…The differences mentioned above cause changes in the heat balance by comparison with the areas surrounding the city. The city heats itself slowly, stores more heat overall, and passes it on again slowly to the surrounding areas, i.e., it can generally be considered an enormous heat storage unit [90,91]. Over the long term, this process increases the annual mean air and soil temperatures.…”
Section: Physical Chemistrymentioning
confidence: 99%
“…Zhou investigated the main coal and gas spontaneous combustion mines in China and found that the main causes for the frequent occurrence of GCSC symbiotic disasters are interaction of the underground mixed gas concentration field, temperature field, and fracture field. Zhu et al , studied the temperature distribution characteristics of the surrounding rock of roadway in the deep coal mine. Li et al , proposed an index of air volume safety regulation range and the judgment condition of composite disaster imbalance and extensively discussed the mutual restriction relationship under the condition of implementing disaster-prevention technical measures.…”
Section: Introductionmentioning
confidence: 99%
“…Rock deformation caused by thermal stress will be constrained by in situ stress, so in situ stress can be used as the boundary load of the rock physical field. With the gradual development of deep mining, thermal stress has become an increasingly prominent problem, which poses a great threat to mine production [1][2][3]. ermal stress is a major factor leading to rock fracture, and its fracture mechanism has received increasing attention.…”
Section: Introductionmentioning
confidence: 99%